Frequency of endoparasites eggs in curly lettuce (Lactuca sativa) sold in markets, open markets and restaurants in Manaus – Amazonas (Research, Society and Development, 2021)
Intestinal parasites represent a serious public health problem in Brazil, and among parasitic diseases, enteroparasitosis are the most common. The eating habit of consuming fresh vegetables allows the exposure of a large portion of the population to transmissible forms of parasites. Lettuce (Lactuca sativa) is the vegetable with the greatest production (ease of cultivation) and consumption (ease of access) in Brazil, as it is part of the Brazilian daily diet. Therefore, the aim of this study was to develop an epidemio-parasitological survey of parasitic forms in curly lettuce (Lactuca sativa) commercialized in markets, open markets and restaurants in Manaus, AM, Brazil. Curly lettuce samples were collected from markets, open markets and restaurants and evaluated for the detection of parasites. In samples from markets and open markets, 100% of the presence of parasite eggs was observed, highlighting the genera Hymenolepis spp. and Entamoeba spp., in addition to a lower frequency of Ascaris spp., Taenia spp., Schistosoma spp. and Toxocara spp. Regarding to the results of restaurant samples, in 50% of them we were able to detect parasite eggs, highlighting the genera Hymenolepis spp., Ascaris spp. and Ancylostoma spp. Thus, based on our results, we can conclude that the curly lettuce sold in markets or open markets in Manaus, during the period of this study, presented 100% contamination by parasite eggs, whereas in 50% of curly lettuce samples in restaurants, theoretically ready for consumption, parasite eggs were also identified.